The Effect of Interactional Teaching Style on Student Participation in Buddhist Religious Education Learning Activities - Mardiono, Mardiono; Andriyaningsih, Ayu; Sutawan, Komang; Wulandari, Ayu (Journal of Education, Religious, and Instructions (JoERI), 2024)
Increasing student participation and engagement is a crucial benefit of interactive education. Education serves as a medium for knowledge transfer and helps society develop critical thinking, self-control, and a strong sense of morality. This study aims to determine the influence of interactive teaching methods on student participation in Buddhist education. This study uses a quantitative approach with survey methods and data analysis using descriptive statistics. The study sample consisted of thirty students selected using a saturated sampling technique. The study's findings show that interactive learning positively and significantly influences student participation. This supports the research hypothesis that interactive teaching methods can increase students' motivation, engagement, and active participation in the learning process. This study shows that although interactive learning significantly impacts student participation, other external factors also affect learning. This approach encourages students to be more active in the learning process through group projects, cooperative learning, and discussions, thereby increasing confidence and class engagement.